2019
DOI: 10.1101/840017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Model Predicts Paracrine and Intracellular Drivers of Fibroblast Phenotype After Myocardial Infarction

Abstract: 2The fibroblast is a key mediator of wound healing in the heart and other organs, yet how 2 3 it integrates multiple time-dependent paracrine signals to control extracellular matrix 2 4 synthesis has been difficult to study in vivo. Here, we extended a computational model to 2 5 simulate the dynamics of fibroblast signaling and fibrosis after myocardial infarction in 2 6 response to time-dependent data for nine paracrine stimuli. This computational model 2 7was validated against dynamic collagen expression… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…RNA was then isolated, and next-generation RNA sequencing was performed. Many genes associated with a manually curated network of fibrosis and fibroblasts 50, 51 were differentially regulated between control and Ror1/2-KO fibroblasts ( Figure 3A ). As expected, cells were largely void of Ror1 and Ror2 transcripts, and the planar cell polarity gene Ptk7, Vangl1, Vangl2, Prickle1, Dvl1, Dvl2, Dvl3 ) were generally reduced in the Ror1/2-KO fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…RNA was then isolated, and next-generation RNA sequencing was performed. Many genes associated with a manually curated network of fibrosis and fibroblasts 50, 51 were differentially regulated between control and Ror1/2-KO fibroblasts ( Figure 3A ). As expected, cells were largely void of Ror1 and Ror2 transcripts, and the planar cell polarity gene Ptk7, Vangl1, Vangl2, Prickle1, Dvl1, Dvl2, Dvl3 ) were generally reduced in the Ror1/2-KO fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…This capability is particularly important in the context of an infarcted left ventricle wherein fibroblasts in the infarct scar are subjected to heightened tensile stretches compared to the fibroblasts in the remote, non-infarcted myocardium that are subjected to normal myocardial tensions (Torres et al, 2018). We investigated this capability by simulating the expression of model outputs in response to valsartan treatment in both low-and high-tension contexts, while setting the model cytokine inputs to experimentally matched postinfarct levels as previously described (Zeigler et al, 2020). We compared model output expressions to a study by Ramirez and colleagues, who observed significant differences in fibrosis-related gene expression between infarct and remote zones and negligible effects of valsartan treatment alone using a mouse model (Ramirez et al, 2014).…”
Section: Fibroblast Signaling Network Predicts Behavior Of Current Pomentioning
confidence: 99%
“…All negative control simulations were conducted using input reaction weights of 0.1, and all input reaction weights and drug perturbation levels for in vitro studies were chosen to maximize the dynamic range of network responses. Input reaction weights for in vivo studies were interpolated from experimental data of cytokine levels post-MI as previously described (Zeigler et al, 2020) using a time point of 4 weeks post-infarction, and tension reaction weights for control and infarct zones were set to 0.1 and 0.6, respectively. All input reaction weights and perturbation conditions can be found in Table 1.…”
Section: Drug Effect Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…We build on our previous literature-validated model of cardiac fibroblast signaling, 27 which has predicted network mechanisms underlying fibroblast phenotype in vitro and during post-MI wound healing. 28 In this study, we create a framework for integrating this fibroblast network model with the drug-target DrugBank database 19 to perform an in silico screen for drugs that are profibrotic or antifibrotic. We validate the predicted drug effects on fibrosis with in vivo studies from the literature, and we further validate the predicted effect of Galunisertib on fibroblast phenotype in vitro.…”
Section: Introductionmentioning
confidence: 99%